The Effect Of Trust On Loyalty Mediated By Customer Satisfaction And Commitment - Budiyanti, Theresia (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze the effect of trust on customer loyalty by mediating customer satisfaction and commitment. This study uses a quantitative approach by collecting data through surveys using questionnaires to respondents who are customers of an organization or company. Data analysis was performed using regression methods to evaluate how trust can affect loyalty, with customer satisfaction and commitment as intermediary variables. The results of this study are expected to provide a better understanding of the relationship between trust, customer satisfaction, commitment, and customer loyalty. The implications may provide valuable insight for business practitioners in developing strategies that increase customer loyalty through increased trust, customer satisfaction, and commitment. This research can also make theoretical contributions to the marketing management literature regarding the relationship between these variables.